Activity of Ethanol Fraction Melinjo (Gnetum Gnemon L.) Seed on Colonic Cancer (Widr) Cells as Co-Chemotherapy Agent - Arifin, Nuha Haifa; Febriansah, Rifki; Octavia, Melany Ayu; Kenyori, Ivana Kinanti (Indonesian Journal of Cancer Chemoprevention, 2023)
Cancer deaths increase every year, including in Indonesia. The low selectivity of chemotherapy agents and the resistance of cancer cells against chemotherapy agents is the main cause of chemotherapy treatment failure. It causes serious side effects in sufferers. Beside that, plants produce secondary metabolites which are being investigated for the anticancer activity that is used as new clinical drugs. Therefore we need research that uses plants as co-chemotherapy agents. Melinjo seeds (Gnetum gnemon L.) contain gnetin C has the potential to apoptosis WiDr colon cancer cells. The purpose of this study was to determine the potential of Ethanol Fraction Melinjo Seed (EFMS) as a co-chemotherapy agent for colon cancer. The sample was maceration using 70% ethanol and fractionated with ethanol. Phytochemical screening with thin layer chromatography (TLC)-Densitometry, antioxidant test used the DPPH, while the cytotoxic activity of WiDr colon cancer cells and their combination with 5-Fluorouracil chemotherapy agent using the 3-(4,-5-dimethylthiazo-2-yl)-2,5-diphenyltetrazolium bromide (MTT) Assay, and also in silico test used molecular docking between gnetin C on EFMS and IKK and COX-2 proteins with the 5-FU. The results showed that EFMS contains gnetin C based on Rf value, has weak antioxidant activity with IC50 1227 μg/mL, weak cytotoxic activity in WiDr colon cancer cells with IC50 681 μg/mL and has combined activity synergistic with 5-Fluorouracil. Molecular docking showed gnetin C strong binding affinity against IKK and COX-2 proteins with scores -12.2 kcal/mol and -9.6 kcal/mol. The result concludes that EFMS has the potential to inhibit the development of cancer cells, especially WiDr colon cancer cells.Keywords: Gnetum gnemon L., Colon Cancer, Cytotoxic, Molecular docking, WiDr.